Does focused endogenous attention prevent attentional capture in pop-out visual search? - Seiss, Ellen (2009)
To investigate whether salient visual singletons capture attention when they appear outside the current endogenous attentional focus, we measured the N2pc component as a marker of attentional capture in a visual search task where target or nontarget singletons were presented at locations previously cued as task-relevant, or in the uncued irrelevant hemifield. In two experiments, targets were either defined by colour, or by a combination of colour and shape. The N2pc was elicited both for attended singletons and for singletons on the uncued side, demonstrating that focused endogenous attention cannot prevent attentional capture by salient unattended visual events. However, N2pc amplitudes were larger for attended and unattended singletons that shared features with the current target, suggesting that top-down task sets modulate the capacity of visual singletons to capture attention both within and outside the current attentional focus.